2017
DOI: 10.1002/cphc.201701015
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Shape‐Memory Polymer Foams with Bio‐inspired Antimicrobials

Abstract: Despite a number of clinically available hemostats, uncontrolled bleeding is the primary cause of trauma-related death. Shape-memory polymer (SMP) foams have a number of desirable properties for use as hemostats, including shape recovery to enable delivery into bleed sites, biocompatibility, and rapid blood clotting. To expand upon this material system, the current work aims to incorporate phenolic acids, which are honey-based antimicrobial agents, into SMP foams. We showed that cinnamic acid (CA) can be utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…epi. [12]. These results provide a proof-of-concept that PAs do not need to be released or solubilized from a polymer network to be functional and indicates that reaction of the carboxylic acid does not affect antimicrobial function.…”
Section: Modified Phenolic Acid Antimicrobial Propertiesmentioning
confidence: 61%
See 1 more Smart Citation
“…epi. [12]. These results provide a proof-of-concept that PAs do not need to be released or solubilized from a polymer network to be functional and indicates that reaction of the carboxylic acid does not affect antimicrobial function.…”
Section: Modified Phenolic Acid Antimicrobial Propertiesmentioning
confidence: 61%
“…PAs are small, simple molecules that contain a carboxylic acid group on their non-active end. This group enables their potential incorporation into a range of polymeric medical devices, including polyurethanes [12]. PAs are secondary metabolites of plants that kill microorganisms and/or inhibit the growth of bacteria as part of the plant antimicrobial mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Combat casualty studies showed that uncontrolled bleeding was the cause of approximately 90% of potentially survivable deaths on battlefields, and severe hemorrhage is the primary cause of battlefield mortality (Eastridge et al, 2011(Eastridge et al, , 2012Holcomb et al, 2007;Sheppard et al, 2015;Wedmore, McManus, Pusateri, & Holcomb, 2006). Current hemostatic treatments include the combined use of pro-coagulantembedded compression gauze with tourniquets (Monroe et al, 2018). However, they are not effective for the treatment of deep and noncompressible wounds, which make up 67% of all hemorrhagic injuries (Holcomb, Stansbury, Champion, Wade, & Bellamy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory polymer (SMP) foams demonstrate great potential in hemostatic applications due to their high biocompatibility, high porosity, large surface area, and unique shape retention property (Monroe et al, ; Landsman et al, ). SMP foams have a highly porous primary shape that can be compressed into a low volume secondary structure when heated above their glass transition temperature ( T g ).…”
Section: Introductionmentioning
confidence: 99%
“…While SMP foams should be compared with these materials in future in vivo studies, the benefit of SMP foams relative to these systems is the reduced cost and effort required to produce a fully synthetic dressing. An additional benefit is the ability to modify SMP foams with functional groups, such as antimicrobial or X‐ray visible monomers 36,37 . in vitro models provide a means for rapid evaluation of the effects of modifications on hemostat use prior to characterization in vivo.…”
Section: Discussionmentioning
confidence: 99%